Surviving state terror: women's testimonies of repression and resistance in Argentina - Sutton, Barbara (New York University Press, 2018)
Women, state terror, and collective memory -- Telling terror -- Narrating the body -- Body, survival, resistance, and memory -- Transmitting memory, reclaiming utopia -- Conclusions and implications -- Acknowledgments -- Notes -- Cited testimonies -- References -- Index -- About the author